2011
DOI: 10.5772/1043
|View full text |Cite
|
Sign up to set email alerts
|

Two Phase Flow, Phase Change and Numerical Modeling

Abstract: Malaysia, Malaysia. He received a Ph.D in Civil Engineering from the University of Fukui, Japan. He has been involved in collaboration research with many researchers and scientists in the world since 2004 and published in diverse areas of Civil and Environmental Engineering. He has published 3 books, 6 book chapters, over 19 technical papers, and is a member of the editorial board of numerous international technical journals. He has been serving on the scientific and editorial board of InTech Open Access Publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 301 publications
0
3
0
Order By: Relevance
“…Surface wettability highly influences the CHF in pool boiling heat transfer. At the intermolecular level, the amount of wettability is also governed by the balance of adhesive forces, which cause the liquid to spread across the surface, and the cohesive forces within the liquid that resist the separation of molecules [ 25 ]. Cohesive forces act between molecules of the same substance, while adhesive forces determine the degree of attraction between molecules of different substances.…”
Section: Literature Results On the Effect Of Surface Wettability On P...mentioning
confidence: 99%
See 2 more Smart Citations
“…Surface wettability highly influences the CHF in pool boiling heat transfer. At the intermolecular level, the amount of wettability is also governed by the balance of adhesive forces, which cause the liquid to spread across the surface, and the cohesive forces within the liquid that resist the separation of molecules [ 25 ]. Cohesive forces act between molecules of the same substance, while adhesive forces determine the degree of attraction between molecules of different substances.…”
Section: Literature Results On the Effect Of Surface Wettability On P...mentioning
confidence: 99%
“…Studies [ 25 , 39 ] have shown that hydrophilic surfaces enhance the CHF by ensuring a continuous supply of liquid to be evaporated, which delays surface dry-out. In contrast, hydrophobic surfaces tend to repel liquids from the surface and form vapour blankets more readily during pool boiling, which deteriorates the CHF [ 30 , 39 , 40 ] but also lowers the ONB, leading to a higher HTC.…”
Section: Literature Results On the Effect Of Surface Wettability On P...mentioning
confidence: 99%
See 1 more Smart Citation